REVIEW DESAIN PERHITUNGAN STRUKTUR PROYEK GEDUNG KANTOR SATPOL PP DI KOTA SAMARINDA - KHAIDIR, RIZAL (KURVA S JURNAL MAHASISWA, 2014)
Shop building collapse in housing Cendrawasih Permai, Sungai Pinang, Jalan A Yani, Samarinda Kal-team to the attention of all parties. The loss and the impact it had very detrimental to all parties, especially the workers and the project is and how much more casualties. The failure which led to the collapse of the construction of this building is concerned suwatu and tarnished the city samarinda. Seventeen three-storey tenement buildings that collapsed suddenly, leavingdebris crushed material. As a result of this incident the need for building design should consider several criteria, including criteria for the power construction, efficient time and cost, power, wind load, seismic calculations, and also other aspects. Multistory building plan in terms of structure requires careful consideration, particularly building up structural work very useable and implemented standards in the world, especially in the field of civil engineering building. In the implementation of this final project with Design Review to be conducted projected Sick Building Office in the city of Samarinda. Up Design Review for comparison of the structure calculations so that the calculations are reviewed planner and will look different because planners 3 floors and converted into 5 floors. Adaiah calculation method of building structures with SAP 2000 program, Manual calculation using the standard Takabeya. Calculation SNI 03-2847-2002 until this calculation